Bioplastic Manufacturing from Durian Rind Cellulose Using the Phase Inversion Method - Caecilia Pujiastuti; Adeela Alvhiani Muharomah (Future Science, 2023)
Plastic waste in Indonesia in 2020 reached around 5.66 million tons, or 17.1% of the country's total waste based on Data from the Ministry of Environment and Forestry of the Republic of Indonesia (2020). Using bioplastics is one solution to this problem. Bioplastics are plastics made from biodegradable materials such as cellulose. Durian rind contains high levels of cellulose (50 - 60%) and lignin (5%). Durian rind cellulose can be extracted through delignification. Phase inversion is a process in which a polymer is changed in a controlled manner from a liquid to a solid state. Phase inversion method is used to make bioplastics from durian rind cellulose with the addition of chitosan and glycerol to test for the effect in mechanical test properties of bioplastic (tensile strength, elongation, swelling and biodegradation tests). Bioplastics are made with variations chitosan levels of 8%, 10%, 12%, 14% and 16% and variations glycerol levels of 1%, 2%, 3%, 4%, 5%. The best bioplastic from durian rind cellulose is the variation of 16% chitosan and 1% glycerol. The bioplastic has a tensile strength value of 1.1603 Mpa, biodegradation of 98.99% in 12 days and swelling (water absorption capacity) of 25.11% and elongation of 12.20. %.